Prosthetic rehabilitation of a child with velopharyngeal dysfunction - A case report - Neha Sikka; Reeta Jain; Ashutosh Kaushik; Reena Rani (Elsevier, 2014)
The speech of person is a unique mode of expression for an individual. Alterations or deviation from normal speech leading to nasal and unintelligible speech have enormous effects on the psychological well being of a person as it hampers social interactions. The anatomic or functional anomalies occurring as a result of congenital or traumatic defects leading to velopharyngeal dysfunctions influence the speech by making it completely atypical. The cleft palate patients may have residual velopharyngeal inadequacy even after surgical repair. A removable palatal lift appliance in conjuction with speech therapy is a viable treatment option for such patients as it is economical, easy to fabricate and easy to use.